Exploring changes in attitudes towards doping in sport in different groups of the russian population: a mixed methods study with policy recommendations - Maria Tarasova; Olga Kulyamina; Evgeniya Bronnikova; Marina Vinogradova; Elena Povorina (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2024)
Introduction: This article examines the evolution of anti-doping culture in Russia through a comparative analysis of sociological surveys conducted in 2019, 2020, and 2021. It focuses on the changing attitudes of Russian citizens towards doping in sports, their awareness of anti-doping regulations, and the underlying causes and motivations for violations of anti-doping rules. The significance of understanding public opinion on doping and countermeasures is highlighted, underscoring its value for specialists, researchers, and executive authorities in addressing and mitigating the issue. Materials and Methods: The study employed sociological surveys across various categories and groups within the Russian population, spanning three consecutive years. These surveys aimed to gather comprehensive insights into the public's perception of doping, knowledge of anti-doping efforts, and attitudes towards the effectiveness of existing anti-doping measures. The methodology was designed to enable a detailed comparative analysis, shedding light on trends and shifts in public opinion over time. Results: Findings from the surveys reveal a noticeable development in the anti-doping culture among the Russian population, marked by changes in attitudes towards doping use and a growing awareness of anti-doping rules. The research identified specific causes and motives behind anti-doping rule violations, illustrating the complex nature of the issue. Additionally, the study provided an objective assessment of the problem's scale, based on the attitudes of various social groups towards the use of banned substances, whether of natural, narcotic, or synthetic origin. Conclusions: The paper concludes with up-to-date data on the anti-doping situation in the Russian Federation and perspectives from scientists on enhancing anti-doping efforts. Based on the analysis, the authors propose a set of measures aimed at improving anti-doping activities in Russia. These recommendations are intended to bolster the fight against doping, reflecting the study's contribution to forming a comprehensive understanding of societal attitudes towards this challenge and paving the way for more effective countermeasures.